PERUBAHAN PENGGUNAAN LAHAN PERTANIAN PASCA GEMPA KOTA PADANG TAHUN 2009 - Edwin Edwin; Adrinal Adrinal (Menara Ilmu, 2020)
Abstract: The earthquake that occurred on 30 September 2009 had an impact on patterns of use of agricultural land and human settlements. Many agricultural lands are turned into residential land, especially the city of Padang. The purpose of this research ; (1). To see patterns and changes in the use of agricultural land in the city of Padang in the aftermath of the 2009 Padang earthquake; and (2) To see the population distribution pattern after the earthquake in Padang City. The method used is spatial and temporal analysis of changes in land use and population distribution before the earthquake and after the earthquake. The results of the study indicate that there has been a change in land use in the City of Padang from 2008-2012. Upland land that is widely used for agricultural business has decreased by 6%. Furthermore, there has been a change in land use in the city of Padang from 20012-2018. The decrease occurred on forest land by 38% and paddy fields by 41%. This decrease occurred due to the conversion of land into settlements which increased to 188%. In 2012, there was a decrease in population, especially in the districts of South Padang, North Padang, West Padang, East Padang and Bungus Teluk Kabung. In other Districts there was an increase, especially those that led eastward. Shifting land cover and the population of the city of Padang affect the Padang City Spatial Pattern. Keywords: Earthquake, Land Use, Spatial Analysis